Belajar Pianika Pada Pembelajaran Seni Musik Di Kelas VIII SMP Negeri 12 Kabupaten Solok Selatan - Al Arif Puji Putra; Syeilendra Syeilendra (SENDRATASIK UNP, 2020)
This study aims to describe efforts to improve the learning of playing melodica for students at SMP Negeri 12 in South Solok Regency. The research uses a descriptive qualitative approach. The object of this research was the Efforts to Improve melodica Learning, at SMP Negeri 12 South Solok Regency, which is contained in the implementation of melodica playing instruction. The data sourced from observations and interviews. The interviews used to collect the data were planned interviews and unplanned interviews. After the data were collected through data collection techniques, the next step done was classifying the data based on their importance. Based on the results of research conducted at SMP Negeri 12 in South Solok Regency, in the subject of Music Arts, there is one of the subjects related to playing Nusantara ethnic songs using a melodica. Melodica is a musical instrument which has an important role in learning music in Junior High Schools. Melodica is not only found in learning but in extracurricular activities such as marching band, and melodica also plays an important role in playing song melodies.